Effectiveness and safety of bipolar ablation of heart arrhythmia. A systematic review with meta-analysis. (19th May 2022) - Farkowski, M; Truszkowska, N; Zielinska, A; Karlinski, M; Futyma, P; Pytkowski, M; Hryniewiecki, T; Maciag, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The National Centre for Research and Development, Poland Introduction: Bipolar radiofrequency ablation (BFRA) emerged as a viable technique of radiofrequency ablation where the standard unipolar approach (RFA) failed. A number of studies describing BRFA were published recently suggesting high effectiveness and acceptable safety of this technology for ablation of ventricular tachycardia in structural heart disease (SHD VT), premature ventricular contractions (PVC) or atrial flutter (AFL). Purpose: We performed a systematic review with meta-analysis of available evidence to assess contemporary evidence on the effectiveness and safety of bipolar ablation of heart arrhythmia. Methods: We systematically searched MEDLINE, EMBASE, and CENTRAL databases from inception to 27 August 2022 for prospective and retrospective studies with or without a control group. We also contacted BRFA experts to obtain information on the most up-to-date studies or conference presentations. Case studies and papers describing technical aspects of BRFA rather than clinical outcomes were excluded. Study quality was assessed using the Newcastle–Ottawa Scale. Results: Out of 1919 records we included 12 studies: one good quality case-control study and 11 low-quality case series without a control group. Studies described 120 patients who received BFRA: mean age 61.9±10.3 years, 81% males, mean ejection fraction 43.2±12.4, SHD 62.6%, ICD/CRT-D 52.2%. Almost all patients were qualified to BRFA due to failure of at least one unipolar RFA. Follow-up period differed between studies and ranged between 1-2 years in most cases. The overall acute effectiveness of BRFA was 88.2% (95%CI 82.5-93.8), I2=6.7%. The overall effectiveness of a first BRFA at the end of the follow-up period was 55% (95%CI 46.2-63.7), I2=7.2%. There was a need for a re-ablation in 21.2% patients (95%CI 11.2-31.2), I2=64%. A subgroup analysis for SHD VT, PVC and AFL yielded similar results. There were 16 serious complications including one surgical intervention and no acute deaths; five patients died during the follow-up, mainly due to heart failure progression. Conclusions: Bipolar radiofrequency ablation may be an effective and safe procedure in selected patients who failed at least one unipolar radiofrequency ablation but the quality of the supporting evidence is generally low.